2017
DOI: 10.1111/cns.12721
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin‐interacting protein induced α‐synuclein accumulation via inhibition of autophagic flux: Implications for Parkinson's disease

Abstract: Our data suggested that TXNIP blocked autophagic flux and induced α-synuclein accumulation through inhibition of ATP13A2, indicating TXNIP was a disease-causing protein in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The LRKK2 hMO also contained higher levels of phosphorylated α-syn in endosomal compartments, and higher expression levels of markers of mitophagy and autophagy. The authors also identified TXNIP [a thiol-oxidoreductase that induces lysosomal dysfunction and DA cell death when overexpressed ( 78 )] as an important mediator of LRRK2 -G2019S pathological mechanisms, and proved that knocking-down its expression reversed the accumulation of phosphorylated α-syn.…”
Section: Modeling Pd In Vitromentioning
confidence: 99%
“…The LRKK2 hMO also contained higher levels of phosphorylated α-syn in endosomal compartments, and higher expression levels of markers of mitophagy and autophagy. The authors also identified TXNIP [a thiol-oxidoreductase that induces lysosomal dysfunction and DA cell death when overexpressed ( 78 )] as an important mediator of LRRK2 -G2019S pathological mechanisms, and proved that knocking-down its expression reversed the accumulation of phosphorylated α-syn.…”
Section: Modeling Pd In Vitromentioning
confidence: 99%
“…Subcutaneous ASC is easily accessible from patents and it can be engineered ex-vivo, expanded, and transplanted subcutaneously in its own environment without provoking immune responses. In addition to diabetes, TXNIP is also known to be upregulated in age-related neurodegenerative diseases such as Alzhemer’s and Parkinson’s diseases and Amyotrophic lateral sclerosis (ALS) [22,23]. In these neuronal diseases, mitochondrial dysfunction, protein misfolding and mitophagy deregulation are known to be critically involved in pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The localization of ATP13A2 within the lysosomal membrane implies that it plays a role in modulating autophagy [ 26 ]; therefore, we analyzed human colon cancer specimens. We found that low expression levels of ATP13A2 are closely related to high expression levels of LC3 and SQSTM1, both of which are degraded by lysosomal acid phosphatase following the fusion of the autophagosome with the lysosome.…”
Section: Discussionmentioning
confidence: 99%